식사대용식을 이용한 초저열량 식사요법이 20대 비만 여성들의 심리적 요인과 삶의 질에 미치는 효과 - 김지영(Kim Jiyoung); 김상연(Kim Sangyeon); 정경아(Jung Kyunga); 장유경(Chang Yukyung); 최형석(Choi Hyeongsuk); 최승(Choi Sung); 박미현(Park Mihyeon); 홍성길(Hong Seonggil); 황성주(Hwang Sungjo) (Hanʼguk yongyang hakhoe chi, 2007)
This study was performed to investigate the effects of very low calorie diet (VLCD) using meal replacements that contain the wild grass extracts based on Samul-tang ingredients on psychological factors and quality of life in the obese women $(BMI{≥}25kg/m^2)$ for four weeks. Seventy five women $(20{≤}age<26)$ participated in this experiment. Subjects were randomly classified three groups: 1) General diet group (GD roup, n=27) consumed 3 regular meals within 600 kcal/day 2) Meal replacements group (MR group, n=27) consumed 1 regular meal and 2 meal replacements within 600 kcal/day 3) Herbal Meal replacements group (HMR group, n=27) consumed 1 regular meal and 2 meal replacements within 600 kcal/day. Physical factors (weight, BMI, fat (%)) of the HMR group significantly decreased more than those of GD and MR groups. Moreover, binge eating habit and environmental factors (surrounding support, emotional reaction, expression of opinion) of the HMR group significantly decreased more than those of GD and MR groups. Psychological factor and quality of life were no significant differences among three groups during the experimental period, because both were significantly decreased in all groups after 4 weeks. Therefore, very low calorie diet using meal replacements that contain the wild grass extracts based on Samul-tang ingredients for 4 weeks was effective on improvement of psychological factor and quality of life as well as weight reduction in the obese premenopausal women.